Coordination failure in repeated games with almost-public monitoring - George J. Mailath; Stephen Morris (Theoretical Economics, 2006)
Some private-monitoring games, that is, games with no public histories, can have histories that are almost public. These games are the natural result of perturbing public monitoring games towards private monitoring. We explore the extent to which it is possible to coordinate continuation play in such games. It is always possible to coordinate continuation play by requiring behavior to have bounded recall (i.e., there is a bound L such that in any period, the last L signals are sufficient to determine behavior). We show that, in games with general almost-public private monitoring, this is essentially the only behavior that can coordinate continuation play.
Keywords: C72; C73; D82; 330; Repeated games; private monitoring; almost-public monitoring; coordination; bounded recall